The impact of urban green areas on the surface thermal environment of a tropical city: a case study of Ibadan, Nigeria - Balogun, Ifeoluwa A.; Daramola, Mojolaoluwa T. (Spatial information research (Online), 2019)
This study assesses the relative impact of green areas on the surface thermal characteristics of an urban area. From this study, the existence of the Park Cool Island (PCI) around the green areas and surrounding zones of the green area was noted, as surface temperatures were lower at the green areas and higher at the outer boundaries. Agodi gardens had the highest vegetation cover of 62.1% and was the area with the lowest mean surface temperature (26.79 °C), while Agugu green area had the lowest vegetation cover of 20.7% and had the highest mean surface temperature (27.75 °C). Green areas with higher vegetation cover percentages had higher rate of change of PCI with buffer distance compared to the other two green areas that had lower percentages of vegetation cover. The green areas were identified for their cooling roles on surface temperature within the urban centres of Ibadan as the surface temperature intensities were of the order of 1–2 °C lower within the 500-m buffer zone. The findings, therefore, brings to light the need for increased greenery within the urban areas of the city, and also provide information for urban planners and designers on the need for green spaces in mitigating heat island phenomenon in the city.